2011
DOI: 10.1097/eja.0b013e32834515ba
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-guided infrapatellar nerve block for anterior cruciate ligament repair: a prospective, randomised, double-blind, placebo-controlled clinical trial

Abstract: Adjunct use of an ultrasound-guided block of the infrapatellar nerve is associated with improved pain relief and an increased number of sleep hours after arthroscopy-assisted anterior cruciate ligament repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 18 publications
2
20
1
Order By: Relevance
“…Uncontrolled pain may hinder mobilization and consequently prolong the rehabilitation period [8]. Previous studies have shown that effective pain control results in better outcomes and decreases the duration of hospitalization [3,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Uncontrolled pain may hinder mobilization and consequently prolong the rehabilitation period [8]. Previous studies have shown that effective pain control results in better outcomes and decreases the duration of hospitalization [3,[8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, ACB shows potential as a primarily sensory block with limited motor involvement. Indeed, the ACB provides analgesia after arthroscopic medial meniscectomy [16] and surgical repair of the anterior cruciate ligament [17]. Furthermore, previous studies demonstrated that ACB improved reported pain scores and reduced opioid requirements when compared with placebo in patients undergoing TKA [18][19][20][21].…”
Section: Introductionmentioning
confidence: 98%
“…Several studies (including two randomized, double-blinded, placebo-controlled trials) have examined the efficacy of a selective nerve block of the IPBSN for treatment of postoperative knee pain [57][58][59][60][61]. Trescot described the use of cryoneurolysis of the IPBSN for knee pain in 2003.…”
Section: Perioperative Treatment For Post-surgical Painmentioning
confidence: 99%
“…A randomized, double-masked, placebo-controlled clinical trial (n = 64) of patients undergoing anterior cruciate ligament repair involved an IPBSN block with levobupivacaine (Chirocaine, Abbott Scandinavia AB, Solna, Sweden) 10-20 min prior to the procedure [57]. At 16-24 h postoperatively, the percent of patients with a pain score higher than 3 (out of 10) was lower in the block group than the sham group (P = 0.0117).…”
Section: Perioperative Treatment For Post-surgical Painmentioning
confidence: 99%